2002
DOI: 10.14310/horm.2002.1172
|View full text |Cite
|
Sign up to set email alerts
|

Glucocortidoid sensitivity assessed in peripheral blood cells do not correlate with the feedback sensitivity of the hypothalamo-pituitary adrenal AXIS

Abstract: Glucocorticoids (GC) affect virtually all organ systems, acting mainly via the glucocorticoid receptor (GR). The immune system is the best characterized tissue for assessing GC sensitivity. It is well established that the immune system GC sensitivity varies widely between normal subjects. However, it remains unclear whether measurements of the immune system GC-sensitivity reflect the GC-sensitivity in other GC target tissues of the same individual. Thus, in the present study we compared the GC sensitivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Others have shown that there is considerable interpersonal variability in glucocorticoid responses 23,25,26,29,30,46,51. Interestingly, serum cortisol did not correlate with genome-wide transcriptional analysis of GR and NFκB-regulated genes 38.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Others have shown that there is considerable interpersonal variability in glucocorticoid responses 23,25,26,29,30,46,51. Interestingly, serum cortisol did not correlate with genome-wide transcriptional analysis of GR and NFκB-regulated genes 38.…”
Section: Discussionmentioning
confidence: 90%
“…Glucocorticoid suppression of inflammatory- induced genes and/or proteins has been commonly used21,24,25,3237,46 but this only assesses one mechanism through which glucocorticoids function. Surprisingly few studies have chosen to use GR upregulated genes 29.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a wide variation in glucocorticoid sensitivity amongst humans (45,46), clinically manifested Cushing's syndrome due to increased sensitivity of tissues to glucocorticoids is an extremely rare condition and its mechanism remains unclear. To date only 3 patients have been studied to this direction: two with spontaneous Cushing's syndrome and one with exogenous Cushing's syndrome.…”
Section: Cortisol Hyperreactive Syndromementioning
confidence: 99%